Understanding the Hadith on Perfume: An Effort to Prevent Sexual Harassment and Protect Women - Harahap, Alwi Padly; Amir, Sulaiman Muhammad; Rahmi, Tutia; Yusuf, M. Fajri; Silalahi, Jonson (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Research on hadith related to perfume often emphasizes the ethical aspects of its use and its implications for personality. However, there has been limited exploration of how these hadiths can serve as tools to prevent sexual harassment and protect women. This study aims to examine the hadith concerning women’s use of perfume from the perspective of preventing sexual harassment and safeguarding women. Employing a descriptive-qualitative method combined with thematic analysis techniques, this research analyzes qualitative data, including narrative and interpretive studies of the hadith texts to uncover their meanings. Additionally, it conducts a phenomenological analysis of social norms regarding women’s use of perfume in society. The findings reveal that the prohibition of women wearing perfume in public spaces aims to protect them from negative attention or harassment, which can stem from certain social norms. The hadith advises women to use perfume thoughtfully and by the situation to avoid potential harm. Furthermore, these teachings highlight the importance of ethics, morality, and respect for women, which can serve as a foundation for promoting their protection in social settings. The contribution of this research is to offer a new perspective on the relevance of hadith in preventing sexual harassment through the principle of caution and to reinforce the role of religion in protecting women both socially and psychologically.